Chitosan-based films with cannabis oil as a base material for wound dressing application - Dorota Chelminiak-Dudkiewicz; Aleksander Smolarkiewicz-Wyczachowski; Kinga Mylkie; Magdalena Wujak; Dariusz T. Mlynarczyk; Pawel Nowak; Szymon Bocian; Tomasz Goslinski; Marta Ziegler-Borowska (Scientific Reports, 2022)
Abstract This study focuses on obtaining and characterizing novel chitosan-based biomaterials containing cannabis oil to potentially promote wound healing. The primary active substance in cannabis oil is the non-psychoactive cannabidiol, which has many beneficial properties. In this study, three chitosan-based films containing different concentrations of cannabis oil were prepared. As the amount of oil increased, the obtained biomaterials became rougher as tested by atomic force microscopy. Such rough surfaces promote protein adsorption, confirmed by experiments assessing the interaction between human albumin with the obtained materials. Increased oil concentration also improved the films' mechanical parameters, swelling capacity, and hydrophilic properties, which were checked by the wetting angle measurement. On the other hand, higher oil content resulted in decreased water vapour permeability, which is essential in wound dressing. Furthermore, the prepared films were subjected to an acute toxicity test using a Microtox. Significantly, the film's increased cannabis oil content enhanced the antimicrobial effect against A. fischeri for films in direct contact with bacteria. More importantly, cell culture studies revealed that the obtained materials are biocompatible and, therefore, they might be potential candidates for application in wound dressing materials.